PENGEMBANGAN KOLEKSI DI UPT. PERPUSTAKAAN UNIVERSITAS UDAYANA - Arianti, Ni Komang Rina; Haryanti, Ni Putu Premierita; Suhartika, I Putu (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2025)
This research aims to examine collection development at the Udayana University Library. The Udayana University Library is one of the higher education libraries, where the community served is the Udayana University academic community which currently serves 14 faculties with 112 study programs. This research uses a descriptive method with a qualitative approach. The data sources used in this research are primary data and secondary data which are then organized, managed and analyzed by converting them into a narrative format that is easy to understand. The results of this research indicate that the Udayana University Library has a collection development policy in written form which is used as a guideline in achieving the stated goals. Procurement carried out at the Udayana University Library is adjusted to the budget obtained by distributing catalogs to each faculty to select the required collections. In carrying out weeding activities, collections that are 5 (five) years old will generally be weeded into collections for subsequent destruction.